Morrey Spaces: Introduction and Applications to Integral Operators and PDE's, Volume II - Sawano, Yoshihiro; Di Fazio, Giuseppe; Hakim, Denny Ivanal (Chapman & Hall/CRC Monographs and Research Notes in Mathematics, 2020)
Morrey spaces were introduced by Charles Morrey to investigate the local behaviour of solutions to second order elliptic partial diﬀerential equations. The technique is very useful in many areas in mathematics, in particular in harmonic analysis, potential theory, partial diﬀerential equations and mathematical physics. Across two volumes, the authors of Morrey Spaces: Introduction and Applications to Integral Operators and PDE’s discuss the current state of art and perspectives of developments of this theory of Morrey spaces, with the emphasis in Volume II focused mainly generalizations and interpolation of Morrey spaces. Features Provides a ‘from-scratch’ overview of the topic readable by anyone with an understanding of integration theory Suitable for graduate students, masters course students, and researchers in PDE's or Geometry Replete with exercises and examples to aid the reader’s understanding